To the Issue of the Competence For- mation Criteria - Y. V. Vorsina; T. A. Snigireva (Russian State Vocational Pedagogical University, 2015)
With the competence approach spreading in education, there is an urgent need for a transition from the knowledge assessment to estimation of the competence formation. The paper provides the criteria for such es- timation; denotes the levels of mastering a competence (unconscious and conscious incompetence, conscious and unconscious competence); demonstrates the option of the complex competence estimation, taking into consid- eration the experts' assessment, students' self-assessment, and the training process complexity and logic. The competence qualimetry is exemplified by the training competence diagnostics (i.e. the ability to recognize and apply the theoretical methods) regarding the cognitive and active components. The paper observes the diagnostic methods including the questionnaires, tests and text analysis. The patterns of feasible diagnostic tasks are given along with the qualimetric results of students' competence. The regular diagnostic procedures provide the opportunity for identifying the gaps in students' knowledge and the lack of necessary skills, and correct, thereafter, the training process accordingly. The research findings might be of interest to the higher school teachers and qualimetry specialists.